Preparation, Characterization and Evaluation of Silver Nanoparticles of Thunbergia Grandiflora and Its Antimicrobial Activity - Pal, Priyanka; Gupta, Naveen; Jain, Shailesh (Journal of Drug Delivery and Therapeutics, 2019)
Nanoparticles are gaining interest in biomedical applications due to its importance such as anti-bacterial, anti-fungal and anti-cancer agents. A conventional method for the synthesis of metal nanoparticles involves toxic reagents which produce harmful by-products and are hazardous to the environment. To overcome these limitations, green synthesis of nanoparticles was established. Eco-friendly methods using plant extracts are gaining popularity due to the abundance of raw materials and the production of non-toxic by-products threatening to the environment. Moreover, the nanoparticles synthesized from the plant extract are cost-effective. In addition, nanoparticles produced by green synthesis methods produce synergetic effect where both the nanoparticles as well as the natural bioactive constituents of the plant influence the biocidal properties. The present investigation evaluates phytochemical screening, antimicrobial, antioxidant activities and green synthesis, characterization of silver nanoparticles and its antimicrobial activity. Three dissimilar solvents viz., petroleum ether, ethyl acetate and methanol were used to prepare crude extracts of T. grandiflora leaves. Antioxidant activity was examined by means of DPPH and reducing power assay method. AgNPs were synthesized by using 1mM AgNO3 solution mixed with leaf aqueous extract of T. grandiflora. The characterization of the prepared AgNPs was done by UV-Vis spectrometry and FTIR spectroscopy. Antimicrobial activity was studied by agar well diffusion method. The phytochemical screening results unveiled the bearing of different phytochemicals viz., flavonoids, alkaloids, saponins, carbohydrates, terpenoids, steroids, tannins and free anthraquinones particularly with relatively high abundance in methanol extract. The total phenolics content of leaves of methanolic extract was (0.058mg/gm), followed by flavonoids (1.080mg/gm). Likewise methanol extract too exhibited effective free radical scavenging and antimicrobial activities were concentration dependent. The characterization results of the prepared AgNPs displayed that the silver nanoparticles are formed and stabilized by plant phyto-constituents and also exhibited virtuous antimicrobial property. Green synthesis process is a pivotal area in nanotechnology and usage of natural resources is the best choice for the making of NPs as a sustainable, eco-friendly, inexpensive and free of chemical contaminant method.